Membrane Fas Ligand Kills Human Peripheral Blood T Lymphocytes, and Soluble Fas Ligand Blocks the Killing - Suda, Takashi (The Rockefeller University Press, 1997)
It has been believed that the Fas expressed on human peripheral blood T cells (PBT) is nonfunctional, because these cells are insensitive to agonistic anti-Fas/Apo-1 mAbs that efficiently kill in vitro–activated T cells and many Fas-expressing cell lines. Here, we demonstrate that membrane-bound Fas ligand (FasL) kills both fresh and in vitro–activated PBT, indicating that the Fas expressed on fresh PBT is functional. In contrast, soluble FasL kills only the latter. Naive T cells in umbilical cord blood do not express Fas, but can be induced to express Fas by IFN-γ or by a combination of IL-2 and anti-CD28 mAb, after which they acquire sensitivity to membrane but not to soluble FasL. Soluble FasL inhibited the killing of fresh PBT by membrane FasL. These results indicate that the shedding of FasL from the membrane is a mechanism for downregulating at least part of its killing activity.